If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -6(w + -6) = 4(w + -8) Reorder the terms: 3w + -6(-6 + w) = 4(w + -8) 3w + (-6 * -6 + w * -6) = 4(w + -8) 3w + (36 + -6w) = 4(w + -8) Reorder the terms: 36 + 3w + -6w = 4(w + -8) Combine like terms: 3w + -6w = -3w 36 + -3w = 4(w + -8) Reorder the terms: 36 + -3w = 4(-8 + w) 36 + -3w = (-8 * 4 + w * 4) 36 + -3w = (-32 + 4w) Solving 36 + -3w = -32 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 36 + -3w + -4w = -32 + 4w + -4w Combine like terms: -3w + -4w = -7w 36 + -7w = -32 + 4w + -4w Combine like terms: 4w + -4w = 0 36 + -7w = -32 + 0 36 + -7w = -32 Add '-36' to each side of the equation. 36 + -36 + -7w = -32 + -36 Combine like terms: 36 + -36 = 0 0 + -7w = -32 + -36 -7w = -32 + -36 Combine like terms: -32 + -36 = -68 -7w = -68 Divide each side by '-7'. w = 9.714285714 Simplifying w = 9.714285714
| 12-3q-9q=-12 | | x-7.1=4.7 | | P+8/2=5 | | 7x-8y=-22 | | 9p+5-p=-7 | | 11=x/9 | | -5x-3(5)=0 | | 6j+8-11=0 | | 140=10d | | 5n+n+10=18 | | 9(x+1)-3(x+1)= | | 17d=68 | | 3r+4r-9=-15 | | .33p+7=12-.67p | | 8(2n-4)=(7n+1)+7 | | y-4=-2(x+2) | | 4x^2-36x+3=0 | | 19-k+9k-7= | | 16q=256 | | 9(x+1)=3(x+1) | | x^6/x^8 | | 5f=-3(8-f) | | x+4-3(x+4)=0 | | C=5/9(81) | | 0/8 | | 11m-6+m-1= | | 4x-5(x+3)=6(x+3) | | 10n+2+9-4n= | | 6y-y-7= | | 11d-6d+6= | | -5(x+4)=-2-5x | | x*6-10=-26 |